Body weight modification experience among adolescents from Saudi Arabia - Gosadi, Ibrahim M. (Frontiers in Public Health, 2024)
Background: Childhood malnutrition is a public health issue in developing countries, leading to a double burden of malnutrition, which is associated with both overweight and underweight.Objective: To assess body weight satisfaction and perception as well as body weight modification experiences, among adolescents from Saudi Arabia.This study utilized a cross-sectional design targeting adolescents who attempted to modify their body weight. A questionnaire was constructed to measure their demographics, body weight satisfaction and perception, and experience concerning their weight modification attempts. The chisquare test was used to assess the association between the ability to modify weight and maintain the modification according to the ability to set an appropriate weight target based on the age and height of the adolescents, method of weight modification, and receipt of support to modify weight.Results: A total of 285 adolescents were recruited. More than half of the sample were female (58%); most respondents were secondary school students (73%). Nearly 45% had abnormal body weight where 12.6% were underweight, and 32.3% were overweight or obese. Most of the recruited sample were unsatisfied with their body weight (63%). Although 52% of the adolescents had a normal BMI, only 35% perceived their body weight as normal. Nearly 75% of the sample were able to modify their body weight. However, a smaller proportion were able to maintain the modification they achieved. The most frequently selected body weight modification method was dieting (83%), followed by exercise (69%). Only 40 adolescents (14%) reported consulting a physician regarding their body weight modification attempts. The most frequently reported source of support for weight modification was the family (51%), while the lowest frequency of support was reported concerning schools' contribution (29%). Upon assessing factors associated with the ability to modify weight or maintain the modification, a higher frequency of adolescents who indicated they employed dieting behavior were able to maintain the modification compared to other weight modification practices (p < 0.05). The findings highlight the importance of collaboration between families, schools, and healthcare services to improve adolescent body image and ensure the adoption of healthy body weight modification practices among adolescents.